P-662 Association between polymorphisms in FSHR and reproductive outcomes following IVF. Secondary analysis of a prospective cohort study in Europe and Asia. (30th June 2022) - Neves, A.R; García, S; Blockeel, C; Arroyo, G; Spits, C; Pham, T.D; Ho, T.M; Tournaye, H; Vuong, N.L; Polyzos, N.P
Abstract: Study question: Does the presence of FSHR variants influence the clinical pregnancy rate (CPR), live birth rate (LBR) and cumulative live birth rate (CLBR) in predicted normoresponders? Summary answer: The presence of at least one G allele in FSHR variant rs6165 is associated with higher CPR and LBR when compared to genotype AA. What is known already: FSHR protein expression has been found in the placenta, umbilical cord, amnion and decidua, suggesting a role in the promotion of a healthy pregnancy. Previous reports have analysed the impact of FSHR SNP rs6166 in pregnancy outcomes with conflicting results, mainly due to the heterogeneity in the inclusion criteria and limited sample size. Moreover, the literature is scarce regarding the association between FSHR SNPs rs6165 and rs1394205 and reproductive outcomes. Our aim is to determine whether FSHR SNPs rs6166, rs6166 and rs1394205 influence the reproductive prognosis following IVF. Study design, size, duration: We performed a secondary analysis of a multicenter multinational prospective study, including 368 patients from Vietnam, Belgium and Spain (168 from Europe and 200 from Asia) from 11/2016-06/2019. All patients underwent ovarian stimulation with fixed-dose 150IU rFSH in an antagonist protocol. Participants/materials, setting, methods: Patients aged <38 years, undergoing their first or second IVF cycle with a predicted normal response (antral follicle count >9 and/or antimullerian hormone >1.1ng/ml) were included. CPR, LBR and miscarriage rate (MR) in the first embryo transfer, as well as CLBR, were compared between the different genotypes of FSHR SNPs rs6166, rs6165 and rs1394205. Main results and the role of chance: A total of 351 patients performed at least one embryo transfer (ET). Enrolled patients had a mean age of 30.5 ± 3.63 years. Mean CPR and LBR in the first ET were 56.1% and 48.4%, respectively. Univariate genetic model analysis revealed a significantly higher CPR in the dominant model for variant rs6165 (46.3% (38/82) for genotype AA vs 59.1% (159/269) for genotypes AG/GG, p = 0.04). No statistically significant difference was found regarding the CPR for variants rs6166 nor rs1394205. Also, no statistically significant difference was found in univariate analysis regarding LBR nor MR for the different FSHR variants. However, multivariable logistic regression analysis adjusted for patient age, BMI, ethnicity, type of embryo transfer, embryo stage and number of top quality embryos transferred revealed a statistically significant higher CPR and LBR for FSHR variant rs6165 genotype GG (adjOR 2.50, 95% CI 1.30-4.81, and adjOR 1.96, 95%CI 1.02-3.78, respectively). No statistically significant differences were found regarding CLBR for FSHR variants rs6166, rs6165 nor rs1394205. Limitations, reasons for caution: The young age of the included patients precludes the generalization of the results to older patients. Also, the results should be confirmed in larger cohorts before being extrapolated to the general population. Wider implications of the findings: Our results demonstrate a previously unreported association between variant FSHR SNPs rs6165 genotype GG and higher CPR and LBR and reinforce a potential role for the genetic background in the prediction of a favorable prognosis following IVF. Trial registration number: not-applicable